Specmaster: an OpenCL‐based peptide search engine for tandem mass spectrometry. (20th June 2013) - Weber, Rick; Jenkins, David D.; Peterson, Gregory D.; Qiu, Judy; Foster, Ian; Goble, Carole; Doallo, Ramón; Plata, Óscar
SUMMARY Graphics processing units and multicore processors are now pervasive in computational sciences and high‐performance computing. Their high arithmetic throughput and memory bandwidth combined with their ever increasing programmability make them suitable for a widening variety of applications. We give a high level overview of Specmaster, a Myrimatch port that can use every open computing language device available in a machine to identify peptides in tandem mass spectrometry data. We then highlight device‐specific optimizations for multi‐core CPUs and graphics processing units as well as describe our framework for implementing these optimizations while still using a single code base. We also provide performance results of Specmaster running on four different architectures and compare these numbers with Myrimatch. Finally, we improve on our existing work by showing Specmaster dynamically load‐balancing on 3 Radeon 7970s and 32 Interlagos 6272 cores as well as comparing the quality of our search results with Myrimatch. Copyright © 2013 John Wiley & Sons, Ltd.